Osip Mandelstam in the Works of Polish Poets - Brio, Valentina (Literatūra, 2020)
This article analyzes poems written by Polish authors about Osip Mandelstam. Fifteen poems by famous Polish authors, such as Artur Międzyrzecki, Wiktor Woroszylski, and Jarosław Marek Rymkiewicz, are examined. Polish poets perceive Mandelstam‘s tragic fate through the prism of the poet‘s image and significance of poetry as they appear in the context of the lives of the Polish literary and cultural tradition. These authors see Mandelstam as a martyr, an outstanding poet. To them, their mission is to bear testimony.
Keywords: Osip Mandelstam; Polish poetry; reception; image of Poets